Osteoporosis and Oral Infection : Independent Risk Factors for Oral Bone Loss - Brennan-Calanan, R M; Genco, R J; Wilding, G E; Hovey, K M; Trevisan, M; Wactawski-Wende, J (Journal of dental research, 2008)
Studies have suggested that oral bone loss is independently influenced by local and systemic factors, including osteoporosis. This cross-sectional study of 1256 post-menopausal women, recruited from the Buffalo center of the Women’s Health Initiative Observational Study, evaluated the influence of oral infection and age on the associations between osteoporosis and oral bone loss. Systemic bone density was measured by dual-energy x-ray absorptiometry. Alveolar crestal height was measured from standardized dental radiographs. Oral infection was assessed from subgingival plaque samples. Total forearm density [β (SE) = −0.931 (0.447), p = 0.038] and presence of Tannerella forsythensis [β (SE) = 0.125 (0.051), p = 0.015] were independently associated with mean alveolar height among women aged < 70 years after confounder adjustment. Women aged 70+ years had worse oral bone loss, in general, but neither bone density nor oral infection was significantly associated with mean alveolar height in this age group. Systemic bone density and oral infection independently influenced oral bone loss in post-menopausal women aged < 70 years.